Gene age and genome organization in Escherichia coli and Bacillus subtilis - Jers, Carsten; Mišetić, Hrvoje; Ravikumar, Vaishnavi; Garg, Abhroop; Franjević, Damjan; Domazet-Lošo, Tomislav; Mijakovic, Ivan (Frontiers in Microbiology, 2025)
Using genomic phylostratigraphy, we examined the organization of Escherichia coli and Bacillus subtilis genomes from the perspective of evolutionary age of their genes. Phylostratigraphy analysis classifies individual genes into age-related bins, called phylostrata. Based on this analysis, several common features emerged in the genomes of the two model bacteria. More recent genes tend to be shorter and are expressed less frequently, or only in specific conditions. In terms of genomic location, new genes are enriched in areas containing prophages, suggesting a link with horizontal gene transfer. Interestingly, while most bacterial transcription regulators belong to the oldest phylostrata, they regulate expression of both older and more recent genes alike. A large fraction of bacterial operons contains genes from different phylostrata. This suggests that newer genes are integrated in the existing framework for regulating gene expression, and that the establishment of new regulatory circuits typically do not accompany acquisition of new genes. One striking difference between E. coli and B. subtilis genomes was observed. About 87.0% of all E. coli genes belong to the evolutionary oldest physlostratum. In B. subtilis, this number is only 71.8%, indicating a more eventful evolutionary past in terms of acquisition of new genes, either by gene emergence or by horizontal transfer.